2014
DOI: 10.1007/s00240-014-0733-5
|View full text |Cite
|
Sign up to set email alerts
|

Retro-renal colon: role in percutaneous access

Abstract: Considering the low incidence, the sample size in our study is small. We recommend multicentric large population-based study to establish the true incidence of retrorenal colon and chances of injury to colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Hopper et al reported that retrorenal colon was found in 1.9 % of 500 patients who underwent abdominal CT scan in a supine position, whereas it was seen in 10 % of 90 patients in a prone position [12]. In the larger series study, retrorenal colon was detected in 2 and 6.8 % of patients in supine and prone position, respectively [13]. Despite this, a recently published meta-analysis showed that the risk of colon injury in prone or supine PNL is comparable [14].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Hopper et al reported that retrorenal colon was found in 1.9 % of 500 patients who underwent abdominal CT scan in a supine position, whereas it was seen in 10 % of 90 patients in a prone position [12]. In the larger series study, retrorenal colon was detected in 2 and 6.8 % of patients in supine and prone position, respectively [13]. Despite this, a recently published meta-analysis showed that the risk of colon injury in prone or supine PNL is comparable [14].…”
Section: Discussionmentioning
confidence: 85%
“…Additional steps include total parenteral nutrition, bowel rest and intravenous broad-spectrum antibiotics (7-14 days) [4,16]. After 7-10 days, a contrast agent is given through the nephrostomy tube, and if no nephron-colonic fistula is seen, the tube may be removed [13,[17][18][19]. The ureteral double j stent is removed after 4-6 weeks [20].…”
Section: Conservativementioning
confidence: 99%
“…Retrorenal colon is also more common in the prone position, occurring in 6.8% of patients compared with 2% in supine patients. 27,28 Across these studies the risk of colonic perforation was 0.25% and was higher for a left-sided puncture in the prone position, with only four perforations occurring in the supine position. Studies have not clearly documented what proportion of patients had prone or supine PCNLs to determine the risk of perforation in each position.…”
Section: Discussionmentioning
confidence: 93%
“…Retro-renal colon (RRC) is found in 2% patients in supine and 6.8% patients in prone position [1]. RRC is one of the most important risk factors for colon perforation during percutaneous access to the kidney [2].…”
Section: Introductionmentioning
confidence: 99%
“…RRC is one of the most important risk factors for colon perforation during percutaneous access to the kidney [2]. Sharma et al [1] estimated that there was a 65% chance of colon injury during percutaneous renal access in cases with RRC detected during computed tomography (CT) evaluation.…”
Section: Introductionmentioning
confidence: 99%